Engineering knowledge combined with the pet bottle rocket launch: experience with public school girls in the municipality of Gurupi-TO (Research, Society and Development, 2022)
This article presents an experience report of a scientific initiation (CI) CNPq project "Elas na Engenharia: Por que não?", with the theme "rocket launching". The strategy used was an intervention in the learning process in engineering and related areas. The study was financed by CNPq, with the participation of Civil Engineering teachers from the University of Gurupi (UnirG) and IC scholarship students from the course, executed in five public municipal and state schools, with the involvement of ATP scholarship teachers and junior IC scholarship girls. The goal was to present to the public school students the importance of the insertion of women in engineering courses, using the launching of rockets with PET bottles and showing in practice the teachings of chemistry, physics, mathematics and showing the steps of the construction and learning process having the problematization as a strategy. The prototypes used were vinegar and baking soda, and also water and compressed air. Both had satisfactory results, but the vinegar and sodium bicarbonate prototypes had greater reach, with contributions as to the awakening of students to the areas of engineering and gender inclusion.